Development of right pass game as support of passing training for students basketball extracurricular of Senior High School 1 Gondang - Yosar Wahyu Ramadhan; Henri Gunawan Pratama (Journal of Science and Education (JSE), 2021)
The lack of variety of training models in basketball extracurricular activities at Senior High School 1 Gondang especially the basic techniques of passing and causing a lack of understanding and mastery of students about basketball passing. So it is necessary to develop this game to improve the understanding and mastery of extracurricular basketball students about the basic techniques of passing. This study aims to develop a product in the form of a basketball passing game through a right pass game for basketball extracurricular students at Senior High School 1 Gondang. This research method is development research which refers to the development model of R&D using the ADDIE method, namely: (1) Analyze, (2) Development, (3) Design, (4) Implementation, (5) Evaluation. The data analysis technique used is analysis using qualitative analysis, while descriptive statistics or descriptive analysis is a type of statistical analysis which intends to describe the characteristics of a sample or population. From the trial results obtained expert evaluation data, namely, game experts 86% (good), basketball experts 88% (good), small group trials 84.7% (very good), and large group trials 87.7% (good). Both trials received good category scores and could be used. With these results, it can be concluded that the right pass game can be used as a support for extracurricular basketball student passing exercises at Senior High School 1 Gondang.